Prototype sistem monitoring status pintu berbasis iot dengan notifikasi web dan telegram - Apriansa Arwandi Panjaitan; Annastia Reza Dzulha; Susilawati Sobur (Jurnal Pseudocode, 2026)
In the era of the Industrial Revolution 4.0, the Internet of Things (IoT) has become an innovative solution for enhancing home security. This study designs and implements an IoT-based monitoring door status system using the ESP8266 microcontroller combined with a magnetic sensor. The system enables real-time monitoring and notifications to users via Telegram and provides door status display through a website. With an integrated alarm feature to prevent unauthorized access, this system is expected to enhance home security at a more affordable cost compared to conventional security systems. Testing results indicate that the system accurately detects door status changes with a notification response time of less than 2 seconds. These findings demonstrate the system’s effectiveness in improving security and user conveniencel.